Neuromarketing in Haute Cuisine Gastronomic Experiences - Mengual-Recuerda, Ana; Tur-Viñes, Victoria; Juárez-Varón, David (Frontiers in Psychology, 2020)
Gastronomic experiences offer a set of stimuli that affect the customer's perception of chef-designed food. This empirical study aims to analyse the influence on the consumer, at a cerebral level, of the stimuli characteristic of a high-level gastronomic experience, in a Michelin starred restaurant. The presentation by the waiter or chef, the plate design, the dish served, the taste of food, interaction or moment in which the food is served are the variables analysed. Through the use of neuromarketing techniques - galvanic skin response to register emotional arousal, eye tracking to identify where consumers look, and electroencephalography to interpret emotional reactions - combined with qualitative research technique (In-depth interviews with all consumers), in order to know the natural and suggested memories, the objective of this research is to determine the emotional impact of the variables analysed against the actual taste of food, obtaining conclusions about each variable in overall experience and allowing the authors to propose a model of order design of dishes, designed by the chef, based on emotions and thereby achieving greater efficiency in results of the experience and the memory of it. Results indicate a favourable influence on emotions when the chef presents the food. Likewise, dishes with special presentation have a greater influence at the level of interest than conventional dishes. It is important to highlight that the levels of emotion and attention fall after the midway point of the experience, due to the duration of the experience. Therefore, the dishes do not have the same emotional impact, despite being as special as at the beginning of the experience.